Autistic spectrum disorder in women : how does gender operate? - Maillard, Anne M; Dini, Sarah; Repond, Gloria; Haarman, Guillaume; Clair, Carole; Jequier Gygax, Marine (Revue médicale suisse, 2024)
Autism spectrum disorder (ASD) is a common neurodevelopmental disorder, that affects both pediatric and adult populations and presents heterogeneously. The understanding of the clinical characteristics of ASD has expanded, in parallel with societal developments, including the integration of the notion of gender in medicine. It appears that individuals affected by this disorder, regardless of their age, are neither detected, diagnosed, nor followed or treated in the same manner depending on their gender. This article proposes to review current knowledge on ASD, its expression based on gender, factors influencing care, and the consequences for patients of exposure to gender bias.